Isolation and identification of lactobacillus sp. from dairy products using pcr method / Nurul Fatin Iskandarshah - Iskandarshah, Nurul Fatin (Faculty of Applied Sciences, 2015)
Lactobacilli are gram positive, facultative bacteria which convert lactose and simple sugars to lactic acid. Species belonging to the genus Lactobacillus are used specifically in dairy products. The main purpose of this study was to isolate the Lactobacillus sp. from the dairy product samples and to identify Lactobacillus sp. in dairy product samples by using PCR method. A total of four samples from dairy products which are yogurt, vitagen, yakult, goat milk and three Lactobacillus sp. strains were used in this study. Dairy product samples were purchased at Econsave supermarket and Lactobacillus strains were obtained from Makmal Halal UNISEL, Selangor. Streak plate method was carried out on MRS agar plates to isolate Lactobacillus sp. from the samples. The genomic DNA from these samples were extracted using RTP® Bacteria DNA Mini Kit and were subjected to PCR amplification for the detection of Lactobacillus species using specific primers. All samples showed positive result of DNA band on agarose gel electrophoresis. The extraction DNA method using RTP® Bacteria DNA Mini Kit is suggested for high quality and more reliable result.